2010
DOI: 10.1007/s11273-010-9175-1
|View full text |Cite
|
Sign up to set email alerts
|

Water source utilization and foliar nutrient status differs between upland and flooded plant communities in wetland tree islands

Abstract: Tree islands in the Everglades wetlands are centers of biodiversity and targets of restoration, yet little is known about the pattern of water source utilization by the constituent woody plant communities: upland hammocks and flooded swamp forests. Two potential water sources exist: (1) entrapped rainwater in the vadose zone of the organic soil (referred to as upland soil water), that becomes enriched in phosphorus, and (2) phosphorus-poor groundwater/surface water (referred to as regional water). Using natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…These two hypotheses are not mutually exclusive to each other, but this study will be focusing on ramifications of the chemohydrodynamic hypothesis. This hypothesis has been supported by previous studies that have shown that tree island plants can use marsh water during the dry season Saha et al 2010). One of the predictions of the chemohydrodynamic model is that since nutrient harvesting is transpiration driven, tree islands with low dry season transpiration will have lower nutrient accumulation rates than tree islands with high dry season transpiration.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…These two hypotheses are not mutually exclusive to each other, but this study will be focusing on ramifications of the chemohydrodynamic hypothesis. This hypothesis has been supported by previous studies that have shown that tree island plants can use marsh water during the dry season Saha et al 2010). One of the predictions of the chemohydrodynamic model is that since nutrient harvesting is transpiration driven, tree islands with low dry season transpiration will have lower nutrient accumulation rates than tree islands with high dry season transpiration.…”
Section: Introductionsupporting
confidence: 57%
“…These results are consistent with the differences in the average water levels and hydroperiod of the marshes surrounding the slough and prairie tree islands. In a previous study using stable isotope ratios as a tracer of water uptake in tree islands, Saha et al (2010) showed that Everglades tree island plants use soil trapped rain water during the wet season and marsh water during the dry season. Our foliar d 13 C results suggest that slough tree island avoid water stress by accessing marsh water supply during the dry season, while prairie tree Table 2 Results of univariate two-way ANOVA examining: seasonal and tree island type effects on foliar d 15 N of 7 tree islands (a), species and tree island type effects on foliar d 15 N of the common species (b), and nested univariate one-way ANOVA examining effects of individual tree islands nested in different tree island types on foliar d 15 N of sawgrass growing near 6 tree islands (c) island plants experience water stress as the surrounding marshes dry out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the stepped nature of WCA3AS impedes that process, drowning out large portions of foraging habitat as water pools below elevation breaks. Knowledge of discontinuous elevation gradients, and perched and depressed areas within WCA3AS and considering them for restoration decisions reduces uncertainty of restoration actions; particularly when hydrology is such an important factor (Fuller et al 2008) and small changes in elevation lead to large differences in water depths and nutrient cycles (Saha et al 2010). …”
Section: Elevation Breakmentioning
confidence: 99%
“…The subtropical climate of South Florida is defined by a distinct seasonality in annual precipitation that shifts between winter (dry) and summer (wet) (Mulholland et al 1997), and thus some species have adapted by seasonally changing the source of the water they utilize. In the wet season, some plants have adapted to use local soil moisture primarily supplied by precipitation for transpiration, while during the dry season, the same plants tap into regional groundwater (Saha et al 2010). Species that are vulnerable to moisture fluctuations are unable to survive these changes.…”
mentioning
confidence: 99%